2016
DOI: 10.1016/j.ceramint.2016.04.125
|View full text |Cite
|
Sign up to set email alerts
|

Solution processing of TiO2 compact layers for 3rd generation photovoltaics

Abstract: Solution processing of TiO 2 compact layers for 3 rd generation p h o t o v o l t a i c s , Ceramics International,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…The use of a typical industrial unit (1 m x 1 m) can enable a faster line speed, equivalent to 5 m/min for a processing time of 12.5 seconds. Whilst NIR heating of TiO 2 [27,28] has been demonstrated previously the m-ZrO 2 and m-carbon had not been previously heated by NIR.…”
Section: Introductionmentioning
confidence: 92%
“…The use of a typical industrial unit (1 m x 1 m) can enable a faster line speed, equivalent to 5 m/min for a processing time of 12.5 seconds. Whilst NIR heating of TiO 2 [27,28] has been demonstrated previously the m-ZrO 2 and m-carbon had not been previously heated by NIR.…”
Section: Introductionmentioning
confidence: 92%
“…These are a result of sample contamination during the manufacturing process. In addition, XPS depth profiling revealed that the Ti layer found on EA is thinner than what might be preferred in PSCs according to literature, estimated to be below 20 nm. However, recent work has shown that highly efficient PSCs utilizing ultrathin TiO 2 electron transport layers in the region of 2 nm are possible .…”
Section: Resultsmentioning
confidence: 78%
“…The similar XRD pattern for the CL TiO 2 and FTO was reported by Charbonneau et al . 36 . The crystalline properties of the TiO 2 CL was further confirmed by observing the morphology of the CL film using an AFM as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%